MARVEL: A wireless Miniature Anchored Robotic Videoscope for Expedited Laparoscopy - Castro, C. A.; Smith, S.; Alqassis, A.; Ketterl, T.; Yu Sun; Ross, S.; Rosemurgy, A.; Savage, P. P.; Gitlin, R. D. (2012 IEEE International Conference on Robotics and Automation, 2012)
This paper describes the design and implementation of a Miniature Anchored Robotic Videoscope for Expedited Laparoscopy (MARVEL) and Camera Module (CM) that features wireless communications and control. The CM decreases the surgical-tool bottleneck experienced by surgeons in state-of-the art Laparoscopic Endoscopic Single-Site (LESS) procedures for minimally invasive abdominal surgery. The system includes: (1) a near-zero latency video wireless communications link, (2) a pan/tilt camera platform, actuated by two motors that provides surgeons a full hemisphere field of view inside the abdominal cavity, (3) a small wireless camera, (4) a wireless illumination control system, and (5) a wireless human-machine interface (HMI) to control the CM. An in-vivo experiment on a porcine subject was carried out to test the performance of the system. The robotic design is a Research Platform for a broad range of experiments in a range of domains for faculty and students in the Colleges of Engineering and Medicine and at Tampa General Hospital. This research is the first step in developing semi-autonomous wirelessly controlled and networked laparoscopic devices to enable a paradigm shift in minimally invasive surgery and other domains such as Wireless Body Area Networks.